Perkembangan Pendidikan Islam di Era Rasulullah Periode Mekkah dan Madinah - Aswati, Fajar; Azman, Wan; Ritonga, Supardi; Nopita, Rini (Universitas Nusantara PGRI Kediri, 2025)
The differences in educational patterns between the Meccan and Medinan phases have not been fully understood, particularly in the context of their application in the modern era. There is a lack of comprehensive studies on the dynamics of Islamic education during these two phases as a foundation for developing current educational systems. This research aims to re-examine these aspects as references and foundations for organizing education in both the present and the future. The method used in this study is a qualitative approach and library research or bibliometric analysis, which processes data based on literature. The library sources for this article include books, classical texts, and journals. Education is one of the mechanisms of life aimed at developing individual potential through teaching, training, and experience. Islamic education propagated by the Prophet Muhammad (PBUH) brought about a significant transformation in Arab society. The Prophet successfully transformed society from a state of ignorance characterized by idol worship and tribal conflicts into a unified community founded on faith, knowledge, and noble character. It can be concluded that the Islamic education introduced by the Prophet Muhammad (PBUH), both during the Meccan and Medinan periods, employed a highly comprehensive and profound approach.